The South China Sea is not an obstacle for Dr. Mohd. Hafizil - Siti Nurfarmy, Ibrahim (2019)
Ts. Dr. Mohd Hafizil Mat Yasin might have to deal with travelling for thousands of miles from Peninsular Malaysia and separated from his loved ones before he could complete his doctorate degree in mechanical engineering (fuel combustion), done on a part-time basis, at the Faculty of Mechanical and Automotive Engineering in Universiti Malaysia Pahang (UMP).